Preoperative differentiation of vagal nerve cervical schwannomas from sympathetic chain cervical schwannomas based on diagnosis score and vascular displacement nomogram - XIANG Shiyu, LI Qiao, SHEN Changqing, GU Yajia, WU Bin (Zhongguo aizheng zazhi)
Background and purpose: Accurate preoperative differentiation between vagal nerve cervical schwannomas (SCCS) and sympathetic chain cervical schwannomas (SCCS) in the neck is crucial because of their different postoperative complication. This study aimed to construct and validate a Diagnosis Score and vascular displacement nomogram for the preoperative differentiation of VNCS from SCCS in the neck. Methods: This cross-sectional study retrospectively analyzed patients with pathologically confirmed VNCS and SCCS at Fudan University Shanghai Cancer Center from January 2017 to April 2022. This study was approved by the medical ethics committee of Fudan University Shanghai Cancer Center (approval number: 1612167-18). Inclusion criteria: ① histopathological diagnosis of VNCS or SCCS through biopsy or surgical resection; ② patients with complete clinic data; ③ availability of preoperative contrast-enhanced computed tomography (CT) or magnetic resonance imaging (MRI) examinations. Patients were excluded for: ① contrast agent contraindications; ② poor image quality; ③ severe artifacts; ④ non-standard scanning protocols. The cohort was randomly divided into training and validation sets in a 7∶3 ratio. Two radiologists (one resident and one attending physician) independently evaluated tumor characteristics (location, size and vascular displacement patterns) on preoperative imaging. Independent predictors were selected using LASSO regression analysis to construct a diagnostic scoring system and nomogram, with model performance evaluated by the receiver operating characteristic (ROC) curve. Results: A total of 110 patients were enrolled, with 77 cases allocated to the training set and 33 cases to the validation set. The age range was 24-78 years, and the mean age was (51.22±12.36) years. There were no statistically significant differences in baseline characteristics including age, gender, tumor location and size between the two patient groups (P>0.05). ICA/ECA splaying was significantly associated with SCCS (P<0.001), while the ICA/IJV splaying was significantly associated with VNCS (P<0.001). Lateral and posterior ICA displacement were significantly associated with SCCS (P<0.001), and medial and anterior ICA displacement were significantly associated with VNCS (P<0.001). Five features including tumor size, ICA displacement direction, IJV displacement direction, ICA/ECA splaying and ICA/IJV splaying were used to establish the Diagnosis Score and nomogram. The nomogram combined imaging features showed favorable preference value for differentiating VNCS from SCCS, with area under curve (AUC) values of 0.953 (95% CI: 0.912-0.994) and 0.939 (95% CI: 0.885-0.993) for the training and validation cohorts, respectively. Conclusion: The Diagnosis Score and vascular displacement nomogram showed favorable predictive efficacy for differentiating VNCS from SCCS in the neck, and might be useful for clinical decision-making.